Effects of Annealing on the Structural and Optical Properties of V2O5 Thin Films Prepared by RF Sputtering for Humidity Sensor Application - Hassan, Bakr F.; Dathan, Mohammed J.; Abdallah, Anas A. (Iraqi Journal of Science, 2021)
In this work, vanadium pentoxide (V2O5) thin films were prepared using rf magnetron sputtering on silicon wafer and glass substrates from V2O5 target at 200 °C substrate temperature, followed by annealing at 400 and 500 °C in air for 2 h. The prepared thin films were examined by X-ray diffraction (XRD), forier transform infra-red spectroscopy (FTIR), UV-visible absorbance, and direct current coductivity to study the effects of annealing temperature on their structural and optical properties. The XRD analysis exhibited that the annealing promoted the highly crystallized V2O5 phase that is highly orientated along the c direction. The crystalline size increased from 22.5 nm to 35.4 nm with increasing the annealing temperature to 500 °C. The FTIR spectroscopy showed the enhancement of the characteristics band for the V2O5 with increasing annealing temperature to 500 °C. The optical study showed that the energy gap for the sample deposited on glass slides decreased from 2.85 eV, for as deposited sample, to 2.6 eV upon annealing the sample to 500 °C. There was a linear dependence between sensitivity and relative humidity (RH) at the range from 25% to 70%, while the behavior was exponential at high RH range.